Impact of testosterone levels and testosterone replacement therapy on men’s health (Journal of Medical Science, 2023)
Various studies have shown that testosterone levels have a heavy impact on areas of a man’s health. Low serum testosterone (and, by analogy, late-onset hypogonadism) may be responsible for such conditions as type 2 diabetes, obesity in the abdominal area, and, most of all, heightened cardiovascular risk (CV). Among other outcomes, researchers have pointed out metabolic syndrome and dyslipidemia, as well as an increased risk of anxiety disorders and major depressive disorders. There have also been reports of testosterone’s influence on fertility, bone mineral density, and the development of polycythemia. Low testosterone can have a variety of effects, all of which increase the risk of premature death by raising inflammatory marker levels. Overly high testosterone, however, has been proven to have a notable influence on men’s personalities, as well as other psychological and social traits, both in endogenously elevated testosterone levels and in patients with a history of anabolic-androgenic steroid use. The last decade’s research on testosterone’s impact on the organism has yielded contradictory results. Therefore, examination and understanding of the influence of its abnormal levels prove essential to not only guarantee the best quality of hypogonadism treatment but also to efficiently prevent any side effects or complications associated with testosterone use.